PENGARUH RELAKSASI AUTOGENIK TERHADAP TINGKAT KECEMASAN IBU NIFAS DI PUSKESMAS PUTRI AYU KOTA JAMBI - Rezzy Dwi Ayu; Diniyati Diniyati; Herinawati Herinawati (NHM PRESS, 2022)
According to data from the World Health Organization, it is estimated that in 2020 as many as 20% of women at some time in their lives experience anxiety disorders. In Indonesia, it was found that the prevalence of postpartum anxiety was 28.7%. Primiparous mothers who experienced severe anxiety levels reached 83.4%. The initial survey at the Putri Ayu Health Center in Jambi City found that 7 out of 10 postpartum mothers had complaints that led to anxiety. This study is a pre-experimental design in the form of a one-group pretest-posttest design that aims to determine the effect of autogenic relaxation on the anxiety level of postpartum mothers at the Putri Ayu Health Center, Jambi City in 2021. The population of this study was 47 respondents. The sampling technique is accidental sampling. The sample of this study amounted to 32 respondents, based on the research criteria. The data analysis of this study was carried out univariate and bivariate using the paired t-test. Autogenic relaxation was performed 3 times for 3 consecutive days. After being given an intervention through an autogenic relaxation video, there was a decrease in the level of anxiety from an average of 30.63 to 26.00. Based on the results of the research on the pretest and posttest, having an average before (mean = 30.63) and an average after (mean = 26.00) with p-value (0.000) < 0.05 then Ho is rejected, Ha is accepted. This means that there is an effect of giving Autogenic Relaxation on the anxiety level of postpartum mothers at the Putri Ayu Health Center, Jambi City in 2021. There needs to be socialization and education about autogenic relaxation during pregnancy to prevent as early as possible the occurrence of anxiety in the postpartum period.